The Effect of Simple Science Experiments on Children's Creativity in Group B at Al-Fiqihiyah Integrated Early Childhood Education Center in Palu - Rahmasari Rahmasari; Amrullah Amrullah; Armina Armina; Besse Nirmala (Journal of Educational Sciences, 2026)
This study aims to describe and analyze the effect of simple science experiments on children's creativity. The method used in this study is a quantitative approach. The type of research used is experimental research, and the data used is quantitative data obtained from observations of children's activities during learning, which is described through data before and after treatment. The data was obtained through in-depth interviews, observations, and documentation. The results and discussion of the study show that simple science experiments have an effect on children's creativity in group B of the Al-Fiqihiyah Palu Integrated Early Childhood Education Center. This can be seen from the results of the recapitulation of observations before the simple science experiments were implemented and the results after the simple science experiments were implemented. after the simple science experiments were implemented in all aspects observed, namely batik with tissue, arranging vowels, and arranging colorful Legos, an average of 55.60% of children were in the category of developing very well, 36.10% of children were in the category of developing as expected, 8.30% of children were in the category of starting to develop, and 0% of children were in the category of not yet developing. Meanwhile, the results of the t-test showed that the calculated t-value was 11.858 with a significance of 0.000. Because sig <0.05, it can be concluded that H0 is rejected and H1 is accepted.